(untitled) (Jurnal Manajemen dan Investasi (MANIVESTASI), 2021)
ABSTRACT Â The purpose of the study was to determine whether there was an effect of compensation on employee performance, work discipline on employee performance, and to determine whether there was an effect of compensation and work discipline on employee performance at the Mayor’s Office of the Regional Secretariat of Palembang City, either partially or simultaneously. The data analysis used in this study was using Statistical Product and Service Solution (SPSS) version 22. The data analysis technique was carried out using the classical assumption test in this study including data normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, linear regression analysis. multiple test, correlation coefficient test, and multiple determination coefficient test, as well as hypothesis testing criteria, namely partial test (t test) and simultaneous test (f test). Based on the results of the output data obtained: (1) Liquidity ratio (current ratio) has a significant negative effect on earnings changes, with a significance value of t (0.005 < 0.05), and tcount < ttable. (2) Solvency ratio (debt to total assets) has an insignificant negative effect on earnings changes, with a significance value of t (0.507 > 0.05), and tcount < ttable. (3) Simultaneously (together) the liquidity ratio (current ratio) and the solvency ratio (debt to total assets) have a significant effect on changes in earnings, with a significant value of the current ratio and debt to total assets (0.007 <0.05) and the value of Fcount > Ftable. Â Keywords: Compensation, Work Discipline, Employee Performance Â Â ABSTRAK Â Tujuan penelitian adalah untuk mengetahui ada tidaknya pengaruh kompensasi terhadap kinerja pegawai, disiplin kerja terhadap kinerja pegawai, serta untuk mengetahui ada tidaknya pengaruh kompensasi dan displin kerja terhadap kinerja pegawai pada Kantor Walikota Sekretariat Daerah Kota Palembang, baik secara parsial maupun secara simultan. Adapun analisis data yang digunakan dalam penelitian ini adalah menggunakan Statistical Product and Service Solution ( SPSS ) versi 22. Teknik analisis data yang dilakukan dengan uji asumsi klasik dalam penelitian ini meliputi uji normalitas data, uji multikolonieritas, uji autokorelasi, uji heteroskedastisitas, analisis regresi linier berganda, uji koefisien korelasi, dan uji koefisien determinasi berganda, serta kriteria pengujian hipotesis yaitu uji parsial (uji t) dan uji simultan (uji f). Berdasarkan hasil output data diperoleh: (1) Rasio Likuiditas (current ratio) memiliki pengaruh negatif signifikan terhadap perubahan laba, dengan nilai signifikansi t (0,005 < 0,05), dan thitung < ttabel. (2) Rasio Solvabilitas (debt to total assets) memiliki pengaruh negatif tidak signifikan terhadap perubahan laba, dengan nilai signifikansi t (0,507 > 0,05), dan thitung < Â ttabel . (3) Secara simultan (bersama-sama) Rasio likuiditas (current ratio) dan Rasio Solvabilitas (debt to tota assets) berpengaruh signifikan terhadap Perubahan Laba, dengan nilai signifikan current ratio dan debt to total assets (0,007<0,05) dan nilai Fhitung > Ftabel. Â Kata Kunci : Kompensasi, Displin Kerja, Kinerja Pegawai